An investigation into notification of childhood tuberculosis and its related implications in the district health authority of Germiston - Sekete, Phetole David (My University, 2014)
Tuberculosis causes more deaths per year than all other notifiable infectious diseases put together. World wide tuberculosis is a highly infectious but preventable disease. Tuberculosis was declared a priority disease in 1996 by the South African Health Department. Commitment was pledged by politicians and health personnel to improve the tuberculosis services rendered in the country. The National Tuberculosis Control Programme (NTCP) ‘s mission, aims and of reducing the incidence of tuberculosis and the suffering it causes among the people of South Africa can be achieved if notification systems are improved. The study was conducted in the Germiston District Health Authority. The area has a population of 680 000. A total of 882 cases of tuberculosis were notified between January 1996 and June 1997, of these 163 were children under 15 years of age. The study was to assess whether tuberculosis notifications and all related records were being handled properly by the GP's clinic/hospital and health personnel and the Greater Germiston Council authorities. A field study was undertaken to determine the adequacy of the community based management of childhood cases. The study showed that the: • Majority of the GP's were not notifying tuberculosis (62%) « GP's and clinic/hospital health personnel were not completing notification forms properly • Clinic/hospital health personnel were not filling up patient record cards properly e Greater Germiston Council officials were not reporting b?rT to the GP’s/clinics/hospitals as evidenced by the blank reply spaces on the notification forms i'7T%) (see appendix 12.6) • Directly observed treatment of children with Tuberculosis we-: gor„ •ally well done, but contact tracing and health education programmes need further attention The researcher was subsequently informed that corrective action would be taken by the authorities to remedy the situation. Overall, the results of the study indicate and highlight the importance of notification of tuberculosis.